IN VIVO RESTORATION AND VOLUMETRIC BODY MASS ESTIMATE OFMAMMUTHUS MERIDIONALIS FROM MADONNA DELLA STRADA (SCOPPITO, L’AQUILA) (Rivista italiana di Paleontologia e Stratigrafia, 2022)
In this contribution we present an in vivo reconstruction and volumetric body mass estimate for the mounted skeleton of Mammuthus meridionalis on exhibit at the east bastion of the Spanish Fortress at L’Aquila (Abruzzo, Central Italy). The reconstruction has been obtained starting from a 3D photogrammetric model of the skeleton acquired via a micro-drones and by digitally adding a percentage of soft tissues according to the conditions observed in wild specimens. By applying to the volume the density range proposed in literature for extant proboscideans we obtain an estimate of the body mass in the adult male specimen ranging from 11.3 t to 11.5 t, with average body mass equal to 11.43 t. In addition, we compare the volumetric BM estimate with the BM predictive values obtained by means of traditional regression equations based on long bones linear dimension and shoulder height. The results confirm that the volumetric method is always preferable if sufficiently complete mounted skeletons are available, since application of regression formulas to single bony element can lead to an underestimation or overestimation up to 130%. As a general indication, weight estimates in extinct tetrapods based on single measures and single bones should be totally avoided, especially in groups morphologically and phylogenetically distant from extant reference taxa.